Direct observation of tunnelled intergrowth in SnO2/Ga2O3 complex nanowires. (4th December 2018) - Rigby, Oliver M; Stamp, Alice V; Hindmarsh, Steve A; Alonso-Orts, Manuel; Nogales, Emilio; Méndez, Bianchi; Sanchez, Ana M
Abstract: β -Ga2 O3 intergrowths have been revealed in the SnO2 rutile structure when SnO2 /Ga2 O3 complex nanostructures are grown by thermal evaporation with a catalyst-free basis method. The structure is formed by a Ga2 O3 nanowire trunk, around which a rutile SnO2 particle is formed with [001] aligned to the [010] Ga2 O3 trunk axis. Inside the SnO2 particle, β -Ga2 O3 units occur separated periodically by hexagonal tunnels in the (210) rutile plane. Orange (620 nm) optical emission from tin oxide, with a narrow linewidth indicating localised electronic states, may be associated with this β -Ga2 O3 intergrowth.